Garis panduan berwudhu' dan solat khusus untuk pesakit - Mohamad Ismail, Mohamad Firdaus; Mohd Arifin, Siti Roshaidai (2019)
This is a guideline can be used by the nurses to educate patients on performing ablution and prayers while they were admitted to the hospital.